Bronchial Artery Embolization in Hemoptysis - Dea Putri Audina; Fathiyah Isbaniah; Dicky Soehardiman; Andi Darwis; Bagus Radityo Amien (Jurnal Respirasi)
Hemoptysis, characterized by bleeding from the lower airways, is classified as mild, moderate, or massive, with massive hemoptysis carrying a mortality rate of 6.5–38%. Tuberculosis (TB) remains the most common cause globally. Management strategies include invasive and noninvasive options, with bronchial artery embolization (BAE) emerging as a cornerstone of noninvasive treatment since its introduction in the 1970s. Bronchial artery embolization provides rapid bleeding control and high success rates for both short- and long-term outcomes. Despite these advantages, recurrence rates range widely from 10–55%, often due to incomplete embolization, vessel recanalization, and collateral vessel development. The procedure employs embolic agents such as polyvinyl alcohol (PVA) particles, gelatin sponges, and tris-acryl gelatin microspheres, with minimal complications such as spinal cord infarction or broncho-esophageal fistulas. Diagnostic tools like computed tomography (CT) and bronchoscopy complement BAE by localizing the bleeding sites, stabilizing the airway, and aiding in definitive management. Bronchoscopy serves diagnostic and therapeutic purposes, employing techniques such as vasoconstrictor instillation, laser therapy, and balloon tamponade to control bleeding. Bronchial artery embolization is particularly effective for patients with life-threatening or recurrent hemoptysis who are unsuitable for surgery, often acting as a bridge to elective interventions. This literature review highlighted the pathophysiology, diagnostic modalities, BAE techniques, outcomes, and challenges involved in managing hemoptysis, emphasizing the role of BAE as a vital, minimally invasive therapeutic option.